Communicative Language Teaching in Aviation Vocational College Context: The Effect of Students’ Learning Perception and Attitude on Their EFL Learning Performance (Universitas Muhammadiyah Yogyakarta, 2024)
This study examines the effect of learning perception and attitude on students' learning performance while implementing communicative language teaching (CLT) in a vocational college. The quantitative study used a survey research method with a cross-sectional design. 270 students participated in the study selected using a voluntarily random sampling technique. These research respondents were among those who had completed intermediate English classes with the amplification of the CLT method. Data were collected using a questionnaire with a four-point Likert's scaling method from very disagree (1) to very agree (4) (α = 0.843). The obtained data were analyzed using ANOVA with the assistance of IBM SPSS 25. Results showed a significant effect of learning perception (β = .890; F = 1018.849; p = 0.000) and attitude on students’ learning performance (β = .850; F = 698.468; p = 0.000). Among the two, learning attitude had been the more influential factor in students' learning performance during the implementation of CLT. This study suggested that CLT could be a catalyst for learning perception and attitude to elevate students' learning performance in the context of EFL teaching in vocational college.